THE EFFECT OF AUDIT COMMITTEE CHARACTERISTICS ON TIMELINESS OF FINANCIAL REPORTING ...... - Alshrife, Fouad Mohammed; Subekti, Imam; Widya, Yeney (Accounting Department, 2016)
This study examines the effects of the audit committee independence, audit committee activity, audit committee competence, and moderating auditor quality on the timeliness of financial reporting in manufacturing companies in Indonesia. The variables used in this study are timeliness of financial reporting, audit committee independence, audit committee activity, audit committee competence, and auditor quality. This study used purposive sampling method with the population of manufacturing companies in Indonesia. The sample used in this study was 92 manufacturing companies listed in Indonesia Stock Exchange (IDX) for the period of 2010-2012. The data of this study were financial statement of the manufacturing companies which were collected from the Indonesia Stock Exchange official website. The hypotheses were tested using hierarchical regression analysis. The results showed that the audit committee independence and the audit committee activity negatively affect the timeliness of financial reporting while these results do not support the agency theory. However, another variable examined in this study, namely competence of the audit committee, is not proven to affect the timeliness of the financial reporting. Similarly, the finding of the moderating variable reveals that the auditor quality strengthens the relationship between audit committee independence and financial report timeliness, and audit committee activity and financial report timeliness. On the other hand, auditor quality does not strengthen the correlation between audit committee competence and timeliness of financial reporting.